Book Review of "The United Nations, Peace and Security: From Collective Security to the Responsibility to Protect" by Ramesh Thakur - Arjun Banerjee (International Journal of Nuclear Security, 2017)
This is a review of the second edition of the book by the writer and former UN man, Prof. Ramesh Thakur, that traces the metamorphoses of UN policies from that of collective security in 1945, when it was founded, to the more contemporary notion of the responsibility to protect (R2P) - the notion that sovereignty entails a responsibility to protect all populations from mass atrocity crimes and human rights violations. Thakur’s book is a critique of UN policies and a revelation of the good, bad, and ugly within the system. However, it conjures up an ultimately optimistic image and has a message for those who may be unbelievers of the relevance of the UN in the modern day. The message is that a balanced path needs to be tread between the realists and the idealists, the cynics and the romantics.